(untitled) (Latin American Journal of Sedimentology and Basin Analysis, 2023)
The San Luis range is part of the Eastern Sierras Pampeanas (Caminos, 1979). It comprises a crystalline basement originated in the Lower Paleozoic, largely during the development of the Famatinian magmatic arc (Sato et al., 2003; Morosini et al., 2017); whose closure by collision would have caused significant cortical thickening and tectonic shortening, through the development of ductile shear belts (Ortiz Suarez and Casquet, 2005; Morosini et al., 2020). In the south-centre of the San Luis range outcrop two stongly folded thin belts of metasedimentary rocks of siliciclastic protolith that reached greenschits metamorphic facies, which has been named as San Luis Formation (Prozzi, 1990; Ortiz Suárez et al., 1992; Perón Orrillo, 2017) (Fig. 1). The aim of the present work is to provide a complete and updated genetic and evolutionary model of the sedimentary protolith of each belt of the San Luis Formation (FSL). The FSLO has a maximum width of 10 km and 40 km length in NE-SW trending, from Estancia Pancanta to 10 km north of La Carolina (Ortiz Suárez et al., 1992; Perón Orrillo et al., 2017) (Fig. 1, 2a); while the FSLE has a maximum width of 5 km and 50 km length in NE-SW trending, from southeast of La Florida to La Totora, near the Las Chacras batholith (Ortiz Suárez et al., 1992; Perón Orrillo et al., 2017) (Fig. 1, 2b). Both of them have tectonic contacts with higher grade metamorphic complexes, through NNE-SSW ductile shear belts where some ordovician igneous bodies have been intruded (Perón Orrillo et al., 2017; Morosini et al., 2021). Their macrostructure comprises a tight folding of few kilometer wavelength, generating axial plane cleavage of NNE direction and subvertical dip (von Gosen y Prozzi, 1996; von Gosen, 1998). The protolith of the FSL is made up of mudstones, sandstones and conglomerates (Ortiz Suárez et al., 1992; Perón Orrillo et al., 2017). This assemblage reached the greenschist metamorphic facies with pressure-temperature conditions of 2.5 – 5.1 kbar and 316° – 416°C in the FSLO, and 3.3 – 4.7 kbar and 261° – 403°C in the FSLE (Prozzi, 1990; Verdecchia et al., 2019). According to the radiometric dating of detrital zircons, the FSLO provenance can be associated with the recycling of pre-Pampean sediments with maximum depositional ages of 550 Ma and 530 Ma (Perón Orrillo et al., 2019), while the FSLE provenance is distinctly Pampean with maximum depositional ages of 515 Ma (Drobe et al., 2009, 2011; Perón Orrillo et al., 2019). It was surveyed in field a total of 12,300 m in twelve stratigraphic sections for the FSLO and 8,200 m in ten stratigraphic sections for the FSLE. Facies analysis was applied on those metasediments and both paleoenvironmental and evolutionary models of the basin were proposed. In order to estimate the thickness and arrangement of the lithosomes in each column, a structural analysis was carried out to determine the style and degree of deformation of the strata. Ten lithofacies were recognized (Table 1, Fig. 3, 4, 5, 6). These were grouped into nine facies associations (Table 2, Fig. 7), which were interpreted according to the deep marine sedimentation models of Mutti (1992) and Mutti et al. (1994), as well as the glacimarine system model of Edwards (1986). The facies associations recognized are: AFI has decimetric thickness; it is formed by apparently tabular strata of massive mud-supported paraconglomerates succeeded by massive mudstones; deposited by cohesive debris flows (Fig. 7a,b,c). AFII is up to metric thickness; it is formed by paraconglomerates of sandy-muddy matrix and open fabric in strata with a net to slightly erosive base, succeeded by fine wackes and laminated mudstones; transported by non-cohesive hyperconcentrated flows and deposited by frictional freezing (Fig. 7d,e). AFIII is up to metric thickness; it is formed by paraconglomerates of sandy-muddy matrix and closed fabric, in strata with erosive base, succeeded by fine wackes and laminated mudstones; transported by non-cohesive hyperconcentrated flows and deposited by gradual segregation due to flow dilution (Fig. 7d,f). AFIV has decimetric thickness and it is formed by lenticular strata of sabulites with normal gradation to coarse wackes, followed by fine wackes (Fig. 7g,h,i); deposited by gravel to sandy turbiditic flows with decreasing density. AFV has decimetric thickness and it is made up of lenticular strata of coarse wackes succeeded by fine wackes and laminated mudstones (Fig. 7j,k); deposited by low-density, large-volume, sandy turbiditic flows. AFVI has decimetric thickness and it is formed by thin wackes in strata with a slightly erosive base succeded by laminated mudstones (Fig. 7l,m); deposited by low-density, large-volume, muddy to sandy turbiditic flows. AFVII has hectometric to kilometer thickness and consists only of laminated mudstones (Fig. 7n,o) deposited by decantation of large volumes of suspended mud from remobilization of the slope headwaters, overflowing of channeled flows, contourite currents or even associated to glacimarine system. AFVIII has centimeter thickness formed by alternating sheets of mudstones and carbonaceous mudstones (Fig. 7p,q) deposited by contourite currents or by fluid mudflows, which transported abundant organic matter from the shelf. AFIX is up to metric thickness, formed by the intercalation of tabular strata of laminated mudstones and laminated pebbly mudstones (Fig. 7r,s,t) which would have been deposited by continuous settling of suspended sediment in low-density plumes associated with events of rain-out of debris, from icebergs and seasonal sea-ice in the zone of maximum proglacial of a glacimarine system. The minimum total sediment thickness of the FSLO has been estimated to be 1,700 m (Fig. 8). Its stratigraphic evolution can be divided into three major intervals: in the lower interval, sandy lobes (AFV – AFVI) associated with channel complexes (AFIV) were installed in an abyssal plain with at least 600 m thickness; in the middle interval a by-pass channel was incised and later filled by glacimarine deposits up to 300 m thick; and in the upper interval, sandy lobes (AFV – AFVI) associated with channel complexes (AFIV) were reinstated in an abyssal plain, with a minimum thickness of 700 m (Fig. 8c). This cyclo-stratigraphic arrangement allows inferring a pause in the normal sedimentation of the abyssal plain system, due to a glacial period, which has been assigned the rank of sequence boundary (Rivarola and Ortiz Suárez, 2008; Perón Orrillo and Rivarola, 2014; Perón Orrillo et al., 2017). The minimum total sediment thickness of the FSLE has been estimated to be 3,100 m (Fig. 9). Its stratigraphic evolution can be divided into two major intervals: in the lower interval sandy lobes (AFV – AFVI) were installed on an abyssal plain with at least 800 m thickness; while during the upper interval it was developed acontinental slope system (AFVII – AFVIII) more than 1,500 m thick, which was periodically eroded and filled by slope channel complexes (AFI – AFII – AFIII – AFIV). This cyclo-stratigraphic arrangement would be consistent with the normal progradation of a slope over abyssal plain (Fig. 9c). The radiometric dating of the detrital zircons (Perón Orrillo et al., 2019) shows clear differences in the source area for each belt, since the FSLO inputs come mainly from the reworking of pre-Pampean sediments at an early stage of the Pampean orogen; while the FSLE inputs come mainly from the reworking of the Pampean orogen in its late stages, with an abundance of sediments supplied by the orogenic roots. They also differ in their maximum age of sedimentation, which is 550 Ma in the lower interval of the FSLO, 530 Ma in the upper interval of the FSLO and 515 Ma in the FSLE. The 20 Ma difference between both intervals of the FSLO, before and after the glacimarine metaconglomerates, reinforces the hypothesis that the latter represent a higher-rank depositional sequence boundary. Therefore the FSLO would have been deposited sometime between the Lower and Middle Cambrian (Terreneuvian - Epoch 2), during advanced stages of the Pampean orogeny; while the FSLE would have been deposited sometime between the late stages of the Pampean and early stages of the Famatinian orogeny, before the latter could become a source area; which would correspond to the middle to late Cambrian (Miaolinginian to Furongian). According to the regional geotectonic context for that period it can be stated that the tectonic environment of deposition was a marine foreland basin, west of the Pampean orogen. Keywords: Deep-Marine system, Glaciomarine system, Famatinian orogeny, Pampean orogeny, Cambrian